2009
DOI: 10.1093/brain/awp229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pedunculopontine nucleus area stimulation on gait disorders in Parkinson's disease

Abstract: Gait disturbances are frequent and disabling in advanced Parkinson's disease. These symptoms respond poorly to usual medical and surgical treatments but were reported to be improved by stimulation of the pedunculopontine nucleus. We studied the effects of stimulating the pedunculopontine nucleus area in six patients with severe freezing of gait, unresponsive to levodopa and subthalamic nucleus stimulation. Electrodes were implanted bilaterally in the pedunculopontine nucleus area. Electrode placement was check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
389
5
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(420 citation statements)
references
References 32 publications
13
389
5
5
Order By: Relevance
“…Vim receives strong inputs from the cerebellum, and the effectiveness of tremor control with DBS at this location is a strong argument in favor of cerebellar involvement in the pathophysiology of tremor. PPN DBS [226][227][228][229][230][231][232][233][234][235][236][237][238][239], alone or in combination with STN or GPi DBS, is currently under study for patients with advanced PD who develop levodopaunresponsive freezing of gait, balance impairments, and falls. DBS of the PPN has been shown to be most effective at low stimulation frequencies [240].…”
Section: Use Of Dbs In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Vim receives strong inputs from the cerebellum, and the effectiveness of tremor control with DBS at this location is a strong argument in favor of cerebellar involvement in the pathophysiology of tremor. PPN DBS [226][227][228][229][230][231][232][233][234][235][236][237][238][239], alone or in combination with STN or GPi DBS, is currently under study for patients with advanced PD who develop levodopaunresponsive freezing of gait, balance impairments, and falls. DBS of the PPN has been shown to be most effective at low stimulation frequencies [240].…”
Section: Use Of Dbs In Pdmentioning
confidence: 99%
“…DBS of the PPN has been shown to be most effective at low stimulation frequencies [240]. However, the location of effective PPN stimulation sites remains debated [e.g., 231,241]. Other groups have targeted the zona incerta and CM in patients with PD [7,59], particularly for tremor or dyskinesias.…”
Section: Use Of Dbs In Pdmentioning
confidence: 99%
“…These studies have lead to variable results (Plaha and Gill, 2005;Stefani et al, 2007Stefani et al, , 2010Mazzone et al, 2007Mazzone et al, , 2008Pereira et al, 2008;Pierantozzi et al, 2008;Alessandro et al, 2010;Peppe et al, 2010;Rauch et al, 2010). In some patients, PPN DBS reduces gait and freezing problems unresponsive to drug and conventional stimulation approaches directed at subthalamic and pallidal targets, reduces falls and occasionally improves patients' state of vigilance and quality of sleep (Pereira et al, 2008;Ferraye et al, 2010). The magnitude of the effects, the exact location of the stimulation electrode and best technique of implantation of DBS leads into this nucleus are still being debated (Aravamuthan et al, 2007(Aravamuthan et al, , 2008(Aravamuthan et al, , 2009Weinberger et al, 2008;Fu et al, 2009;Shimamoto et al, 2010).…”
Section: New Targets For Dbs In Pdmentioning
confidence: 99%
“…Ferraye et al reported an open-label study of bilateral PPN stimulation in six PD patients who had previously undergone STN DBS, but with gait and postural problems unresponsive to STN DBS. 125 There was significant improvement in freezing of gait and falls at one year compared to baseline, but blinded on and off stimulation comparisons at one year failed to demonstrate any difference in gait or posture.…”
Section: Dysfunction In Pdmentioning
confidence: 88%
“…123,124 Subsequent reports, unfortunately, are not as impressive. [125][126][127] Moro et al reported six patients with PD who underwent low frequency unilateral PPN stimulation and demonstrated improvements in falls and freezing of gait at 3 months compared to the baseline "off medication" state. 126 There were, however, no improvements in the UPDRS total motor or in gait/posture scores.…”
Section: Dysfunction In Pdmentioning
confidence: 99%